It came from beneath the sink! - Stine, R. L. (New York : Scholastic, 1995)
Kat and Daniel are excited about moving into a new house with tons of rooms, but something evil is lurking in the kitchen.
"An Apple paperback."
"A Parachute Press book"--T.p. verso.
RL4.
008-012.
430
Accelerated Reader AR
Keywords: Monsters -- Juvenile fiction; Horror tales